A presumptive case of cerebral babesiosis in a dog in Poland caused by a virulent Babesia canis strain - Adaszek, L.; Górna, M; Klimiuk, P.; Kalinowski, M; Winiarczyk, S. (Tierärztliche Praxis Ausgabe K: Kleintiere / Heimtiere, 2012)
The aim of this paper was to present the first case of cerebral canine babesiosis due to infection by Babesia canis in a dog in Poland. A 5-year-old American Staffordshire Terrier was presented with an unusual clinical manifestation of acute babesiosis that included neurological signs and pancytopenia. Despite treatment the dog died. Diagnosis was based on microscopic examination of Giemsa-stained blood smears (detection of piroplasms in red blood cells) and post mortem examination of the brain by histopathology and PCR method. The amplified segment of the Babesia 18S RNA gene was sequenced. This enabled to determine that the cause of the disease had been the strain 18S RNA-B EU622793. This is one of two B. canis strains found endemically in Poland, which reveals a greater virulence than the strain 18S RNA-A EU622792. The described case indicates that this form of canine babesiosis should be taken into account in differential diagnosis in dogs exhibiting neurological symptoms, especially in the tick activity season.
Keywords: Babesia canis; cerebral babesiosis; dog; PCR; vector-borne diseases